Genetic resistance to rust of Eucalyptus urophylla progenies - Carignato, André; de Moraes, Cristiano Bueno; Zimback, Léo [UNESP]; Mori, Edson Seizo [UNESP] (FapUNIFESP (SciELO), 2018)
This study assessed the genetic variability in open-pollinated progenies of Eucalyptus urophylla for resistance to rust (Puccinia psidii). The progeny trial was conducted on a statistical randomized block design with 20 progenies, five plants per plot, and nine replications. Analysis of variance showed high genetic variability for the studied trait, with potential for selection gains. The genetic variability of this population provides support to conduct a breeding program with superior individuals for rust resistance, allowing low costs and minimizing the yield losses on eucalyptus plantations.
Keywords: Disease; Genetic parameters; Progeny trial